Automated left atrial strain after electrical cardioversion for atrial fibrillation. (4th February 2022) - Orphanou, N; Zamfir, T; Siama, A; Michelinakis, N; Tsoukas, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Evidence shows that atrial dysfunction and stunning occur, after successful cardioversion from persistent atrial fibrillation (AF) to sinus rhythm (SR). Electrical and mechanical recovery of the left atrium (LA), do not seem to coincide. Traditional Doppler parameters show reduced atrial contractility immediately after cardioversion, while mechanical improvement in atrial function mainly occurs within the first 4 weeks after sinus rhythm restoration. Purpose: This study aimed to determine whether automated left atrial strain (auto-LA strain) could be used to measure global LA function and the time required for mechanical improvement to be seen in LA after cardioversion. Methods: Auto-LA strain was measured via transthoracic echocardiography in 20 patients with persistent AF who had been cardioverted to SR and followed up for 3 months, and in a cohort of 20 healthy individuals. Conventional measures of atrial function derived from transmitral pulsed Doppler and tissue Doppler imaging of lateral mitral annulus were included, such as transmitral A wave velocity, A wave velocity-time integral, atrial fraction, A" wave velocity, and A" velocity-time integral. Results: Immediately after cardioversion auto-LA strain was significantly lower than in control subjects. Atrial function improved over time with maximal change observed at 1 month after cardioversion. Doppler tissue imaging parameters were also normalised after 1 month of restoration to SR. Despite this initial improvement in LA function, the values of auto-LA strain remained stable for the following 3 months. Conclusion: Although the electrical function of LA is immediately restored after successful cardioversion in AF patients, there remains a persistent degree of atrial dysfunction for at least 3 months. This difference could explain the increased propensity for these patients to develop recurrent atrial fibrillation. Additionally, this dysfunction could indicate longer-term use of anti-arrhythmic and antithrombotic medications in the AF cohort.